The algorithm of the formation control of a swarm of autonomousmobile robots - Kyzyrkanov , Абзал; Atanov, Сабыржан; Aljawarneh, Шади; Tursynova, Назира; Seitbattalov, Жексен (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2023)
One of the most important problems in swarm robotics is coordination of the movement. Several problems have to be solved simultaneously here, such as avoiding collisions with each other or with an obstacle, etc. One of the most common methods for solving such problems is to move while maintaining a certain geometric pattern, or, in short, to form control. If formation control is done properly, many benefits can be obtained, such as system cost reduction, increased system robustness and efficiency, while providing the reconfigurability and flexibility of the system structure. This paper presents an algorithm for controlling the formation of a swarm of autonomous mobile robots. Also within the framework of this work, using a software application written in the Python programming language, the motion of the swarm with nine autonomous robots was simulated. The results of the experimental research of the movement of this swarm of robots using the algorithm described in this paper are given.